W sprawie nadania praw miejskich Tykocinowi w XV w. - Sierba, Michał (Acta Universitatis Lodziensis. Folia Historica, 2015)
The article describes an issue of granting the city rights to Tykocin in 15th century. Thanks to insightful analysis of the preserved documents, the hackneyed opinion that the first city rights were given to Tykocin in 1425, is being called into question. In the article all the most important documents about this issue were pointed and described. Basing on those documents we cannot define the exact date of granting the city status to Tykocin for the first time, but it was before 1423. The article also presents all the rights and duties which were guaranteed to the townsmen and the mayor of Tykocin. A biography of the first tykocinan mayor – Peter from Gumowo is showed at the end of the article.